Kajian Nilai Edukasi Tari Tanggai pada Pembelajaran Seni Budaya di SMA Pusri Palembang - Aprilianti, Hesti; Hera, Treny; Kurniawan, Irfan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
Art education in schools is essentially a process of learning activities to develop meaningful values inhumans through art learning. The values referred to are related to the development of imagination,intuition, thought, creativity and sensitivity to taste. This study aims to determine the Study of Educational Values of Tanggai Dance in Cultural Arts Learning at Pusri Palembang High School on the results of cultural arts students. Learning Tanggai dance focuses in this study on educational value. which is seen from the meaning of motion or dance Tanggai. In this study, the method used was descriptive qualitative. The population in this study was Tanggai dance in cultural arts learning which was studied in class x at SMA Pusri Palembang consisting of 14 students. formed into 2 groups. Data analysis techniques in this study consisted of observation, interviews, and documentation. The results showed the educational value of tanggai dance for cultural arts learning at SMA Pusri Palembang, forming students' personalities asindividual, social, religious, and cultural beings.